ANALYZING COHESION IN THE LYRICS OF THE SONG" TERANG BULAN "BY ALM. DJAGA DEPARI - Pandia, Dies Natalia (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2020)
This study discusses the use of cohesion markers in the lyrics of the song "Terang Bula" by the late Djaga Depari. The aim is to describe the shape of the marker Grammatical cohesion and lexical cohesion between lyrics in the song. This research is a qualitative descriptive study. Subject on This research is the song "Terang Bulan" by the late Djaga Depari. The object of this research is the whole form of cohesion markers contained in the songs "Terang Bulan" by the late Djaga Depari. Data obtained by reading and taking notes. The results showed that The form of markers of grammatical cohesion and lexical cohesion found in the song “Terang Bulan” is in the form of a) exophore reference and endophore reference, b) substitution, c) ellipsis, d) conjunction, and e) reiteration in terms of repetition.